The Impact of Vlog Content on Students’ Speaking Skills, Perceptions, and Behavior - Sagita, Velina Cindy; Iman, Fitri Shofi Nur; Hanafi, Muhammad; Tarihoran, Naf’an (Teaching English as Foreign Language, Literature and Linguisticss, 2026)
This study examines the impact of vlog content on students’ speaking skills, perceptions, and learning behaviors in English learning. Using a quantitative descriptive design, data were collected from 150 students in the English Language Education Program at a state Islamic University in West Java through a Google Forms questionnaire consisting of seven Likert-scale statements. The results indicate that most students responded positively to the use of vlogs as a learning medium. Vlogs significantly improved students’ speaking abilities, especially in confidence, fluency, and vocabulary. Exposure to authentic English content helped students better understand pronunciation, intonation, and real-life language use, encouraging more frequent speaking practice. Additionally, students perceived vlogs as engaging, enjoyable, and less monotonous than traditional methods. The audiovisual format supported flexible and independent learning. Moreover, vlogs influenced students’ learning behaviors by increasing motivation, participation, and autonomy. Overall, vlog content proves to be an effective and innovative tool for enhancing speaking skills and promoting active learning.